Hakon of Rogen's Saga - Haugaard, Erik Christian (Book collections on Project MUSE., 2013)
An American Library Association Notable Book and his first book for children, Erik Christian Haugaard's Hakon of Rogen's Saga is a remarkable novel that perfectly catches the mood of a harsh but heroic people. Set at the end of the Viking period, it tells of a young boy, Hakon, from the island of Rogen who, after his chieftain father is murdered, undertakes to reclaim his birthright from his treacherous uncle. The illustrations by renowned artists Leo and Diane Dillon make this captivating story come alive.